Social Modification With The Changing Technology in The Case of Simplification Theory - Ülker, Rana Nur; Turhan, Büşra (European Journal of Sustainable Development, 2014)
Mc. Luhan’s told “The world become global village” came truth. The global village, which main tools are mass media technologies, especially internet, made civilization socials. With the rise of the global communication, every new inventions can be known easily and the technology can be observed. As Marcuse said that the global communication not only makes people same but also simple. Tools are being simple which is understood by everybody from every civilization indeed every age period. In this study, we try to debate this matter, why and how “simplification theory” can make people and technology simple. The simplification theory can be defined as when the media technologies are changed, peoples values and overlook of world are modified. Due to fact that societies’ value and argument about the world translated technologic devices. To sum up, all the instrument of the about human being has changed. Key words: Simplification, Social Modification, Mass Media, Technology, Globalization